Estimation of a regionalized Mexican Social Accounting Matrix: using entropy techniques to reconcile disparate data sources - Harris, Rebecca Lee (International Food Policy Research Institute, 2002)
This paper presents the construction of a 1996 regionalized Social Accounting Matrix (SAM) for Mexico. The SAM differentiates production across five regions, four rural and a fifth "national" urban region. The rural regions are differentiated by their agricultural production technologies. There are three households in each region, disaggregated by income level, so that the SAM can be used in studies of income distribution. The data come from a variety of sources, including Mexico's System of National Accounts, the National Survey on Household Income and Consumption, and the Secretary of Agriculture, Livestock and Rural Development. As a result, the data are not consistent and the "adding up" constraints of the SAM are not met. The SAM is then estimating using entropy techniques to incorporate the data in a consistent way."